(untitled) (Zoological Records and Reviews, 2023)
Niche partitioning – the differential use of resources, space, or time among co-occurring species to reduce interspecific competition – is a fundamental mechanism maintaining species diversity in ecological communities. Amphibian assemblages, where multiple species co-occur in shared wetland and forest habitats during the breeding season, provide tractable systems for examining niche partitioning along multiple dimensions simultaneously. This study examines habitat preference and niche partitioning in 32 co-occurring amphibian species across seasonal wetland, forest stream, and rocky hill habitats of the Eastern Ghats in Andhra Pradesh and Telangana, India, using multivariate microhabitat characterisation, acoustic niche analysis, and temporal activity profiling at 24 sites surveyed over two monsoon seasons (2021-2022). Habitat partitioning is documented along five niche axes: breeding microhabitat (standing water vs. stream vs. terrestrial), calling site height, calling frequency (Hz), temporal calling activity pattern, and larval microhabitat. Niche overlap analysis confirms significant partitioning along all five axes, with acoustic niche partitioning (calling frequency and timing) the strongest axis separating co-occurring species. Species pairs with high habitat overlap show significantly lower acoustic overlap than expected by chance, confirming acoustic character displacement. Microhabitat humidity, temperature, and vegetation structure are the strongest predictors of individual species microhabitat selection. Climate change implications for acoustic niche disruption and interspecific competition are discussed.